Performance of a station-managed N'Dama herd in The Gambia - Njie, A.; Agyemang, K. (Springer, 1991)
Data collected on N'Dama cattle from a government station at Yundum, The Gambia were analysed for a range of performance traits recorded. Influence of environmental and genetic effects on reproductive and productive performance traits were evaluated. Weight, calving interval, calving, liveweights at birth and at weaning, weight gain, growth rates, calf mortality in relation to age, sex and period of calving were examined.